1983
DOI: 10.1289/ehp.8347201
|View full text |Cite
|
Sign up to set email alerts
|

Metallic elements in fossil fuel combustion products: amounts and form of emissions and evaluation of carcinogenicity and mutagenicity.

Abstract: Metallic elements contained in coal, oil and gasoline are mobilized by combustion processes and may be emitted into the atmosphere, mainly as components of submicron particles. The information about the amounts, composition and form of metal compounds is reviewed for some fuels and combustion processes. Since metal compounds are always contained in urban air pollutants, they have to be considered whenever an evaluation of biological impact of air pollutants is made. The value of currently used bioassays for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(39 citation statements)
references
References 161 publications
0
37
0
Order By: Relevance
“…Those samples show a progressive increase in REE, reaching a maximum sum REE/Sc ratio ($50) in the sample found at 1937 AD, at the end of the Industrial Revolution interval (Table 1a). Such REE enrichment is explained by intensive coal combustion over this time interval, coals being characterized by a global REE enrichment (e.g., American coals - Vouk and Piver, 1983). Indeed the Misten samples point towards the average ratio of three main Belgian coal ores (mean sum REE/ Sc = 120).…”
Section: Source Of Dustmentioning
confidence: 89%
“…Those samples show a progressive increase in REE, reaching a maximum sum REE/Sc ratio ($50) in the sample found at 1937 AD, at the end of the Industrial Revolution interval (Table 1a). Such REE enrichment is explained by intensive coal combustion over this time interval, coals being characterized by a global REE enrichment (e.g., American coals - Vouk and Piver, 1983). Indeed the Misten samples point towards the average ratio of three main Belgian coal ores (mean sum REE/ Sc = 120).…”
Section: Source Of Dustmentioning
confidence: 89%
“…DEP consist of carbonaceous nuclei and a vast number of organic chemical compounds such as polyaromatic hydrocarbons, aliphatic hydrocarbons, heterocycles and quinones [26,28,29]. Previous in vitro studies have indicated that exposure of macrophages to organic chemicals extracted from DEP increases the oxidative stress-inducible protein haeme oxygenase-1 [12] and results in induction of apoptosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…volcanic eruptions and forest fires) (Bandara et al, 2008) and anthropogenic activities (e.g. non-ferrous metals production (Vromman et al, 2008), electroplating (Islamoglu et al, 2006), manufacturing of NieCd batteries and pigments (Fthenakis, 2004), application of phosphate fertilizers (Mortvedt and Osborn, 1982), and burning of fossil fuels (Vouk and Piver, 1983)). Pb also is emitted from natural sources and anthropogenic activities (e.g.…”
Section: Introductionmentioning
confidence: 99%